Preferência por direcionalidade na interpretação do par linguístico Libras-português: análise dialógica dos discursos de estudantes da graduação e de intérpretes profissionais - Magno, Letícia Hildebrand (Universidade Federal de São Carlos, 2024)
The research's general objective is to analyze discourses about directionality in interpretation between professional Libras-Portuguese interpreters and undergraduate students of Libras-Portuguese translation and interpretation. Articulating research in the specific and emerging field of study ETILS with the dialogical perspective of language founded by Bakhtin and the Circle, we seek to explore the formative and subjective dimensions of the professional, without disregarding sociocultural aspects and the effects of language modality. As specific objectives, this research proposes (i) to prepare a qualitative comparison between the preferences of the two groups, correlating the information obtained; (ii) bring a discursive analysis of the interviews carried out; (iii) promote a discussion about preference and the historical moment of training and performance/practices. An individual semi-structured interview was carried out remotely, with a student of the TILSP course (UFSCar) regularly enrolled in the last period and an interpreter who has been working for at least 5 years, but without specific professional training in the area. Based on the results observed/found through the transcription and vertical and horizontal analysis of the statements, we propose a reflection to institutions and interpreters, active and in training, so that they pay attention to the necessary skills required in interpretation, no matter which directionality we refer to. We assume that the linguistic effectiveness inherent to the work of the bimodal bilingual interpreter permeates social and methodological transformations of teaching in the academic sphere.
Preference for directionality in the interpretation of the Libras-Portuguese language pair: dialogic analysis of the discourses of undergraduate students and professional interpreters
Keywords: Interpretação; Libras; Português; Direcionalidade; Língua de Sinais; LINGUISTICA, LETRAS E ARTES::LINGUISTICA